Maternal and perinatal outcome in women with threatened abortion in first trimester - Sarmalkar, Meenal S.; Singh, Shashibala; Nayak, Arun H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Threatened abortion in first trimester is a risk factor for complications in the latter half of pregnancy. The present study was undertaken to identify the pregnancy outcome in women with threatened abortion in the first trimester of pregnancy in a tertiary hospital. Methods: A retrospective-prospective observational study was done on 100 pregnant women with a history of threatened abortion in the first trimester. Maternal outcome in the form of pregnancy loss, APH/PPH, Preeclampsia/eclampsia, PROM/PPROM, term delivery and retained placenta were studies. Perinatal outcome in the form of preterm delivery, Low Birth Weight, IUGR and IUFD were studied. Analysis of the data was done using SPSS version 17. Results: Threatened abortion in first trimester was found to be associated with increased risks of LBW, preterm births, PPROM, and PIH. Out of 100 patients, preterm births and LBW babies were found in 21% and 13% of patients respectively. 15% of the cases developed PIH, out of which gestational hypertension and pre-eclampsia were 8% and 6% respectively. Conclusions: Pregnant women with first trimester threatened abortion are at increased risk for spontaneous loss and adverse pregnancy outcomes. Knowledge of these risks may help the obstetricians to manage these cases vigorously in the antepartum period and do timely interventions as needed for a healthy mother and baby.